Sistem Informasi Manajemen Inventori Berbasis Website Untuk Proses Operasional PT Bumi Bara Sakti: Bahasa Indonesia - Asfian, Faeqal Hafidh Muhammad; Desti Fitriati (Journal of Informatics and Advanced Computing (JIAC), 2024)
Inventory plays a crucial role in the operational management of companies, ensuring smooth supply chains and business continuity. Bumi Bara Sakti (BBS), a coal trading company, relies on accurate inventory management. But, BBS faces difficulties in managing inventory data due to a high volume of transactions, leading to heavy workloads and information delays. Additionally, limited Excel proficiency among BBS executives and employees deepens these issues. This study aims to create a web-based Inventory Management Information System using the waterfall method, MySQL for database management, and CodeIgniter4 as the framework. The research mainly focuses on recording coal sales and purchases, total stock, and truck movements to stockpiles based on data obtained from BBS. The system is expected to facilitate real-time recording of purchases, sales, and stock updates while maintaining information accuracy. Furthermore, it provides data visualization and easily understandable reports. Evaluation results indicate that the Inventory Management Information System simplifies inventory data management and data interpretation for BBS executives and employees.